Seasonal chemical composition and antioxidant activity of the essential oil from Cinnamomum zeylanicum Nees leaves in a Brazilian Cerrado region - Lima, Lorena Gonçalves; Sousa, Jéssica Ferreira; Menezes Filho, Antonio Carlos Pereira de; Ventura, Matheus Vinícius Abadia; Rocha, Elizabete Nunes da (Brazilian Journal of Science, 2024)
Cinnamomum zeylanicum is an aromatic species with essential oil in its leaves, stems, and roots, widely used in traditional medicine and culinary applications. The essential oil of C. zeylanicum exhibits various biological activities, such as antioxidant and antifungal properties. This study aimed to evaluate the essential oil extracted from the leaves of C. zeylanicum collected during two seasonal periods in the Brazilian Cerrado, focusing on its volatile chemical profile, and antioxidant, and antifungal activities. Leaves of C. zeylanicum were collected in July and December 2023. The essential oil was extracted through hydro distillation. The volatile chemical profile was determined by gas chromatography-mass spectrometry (GC-MS), antioxidant activity was assessed by DPPH free radical reduction, and antifungal activity was evaluated based on the inhibition of Sclerotinia sclerotiorum, Colletotrichum gloeosporioides, and C. acutatum. Two major compounds were identified: eugenol (72% and 63%) and eugenyl acetate (9% and 15%) for the dry and hot seasons (July) and the wet and hot seasons (December), respectively. DPPH free radical reduction showed maximum inhibition of 89% and 65% for July and December, respectively. Antifungal activity demonstrated maximum inhibition rates of 65% and 53% for S. sclerotiorum, 82% and 71% for C. gloeosporioides, and 56% and 27% for C. acutatum during the same periods. This study highlights seasonal variations in the major compounds of essential oil, which influenced its production, DPPH radical scavenging activity, and inhibition of the evaluated fungal strains.